Microsoft PowerPoint 2010 ([Place of publication not identifed] : [publisher not identified], 2011)
Visual guide to Microsoft PowerPoint 2010 is the latest and up to date educational tool in studying computers. It is presented with full illustrations for the students to easily understand the technology that they are studying.
MS PowerPoint basics -- Creating a presentation -- Working with texts -- Designing a presentation -- Working with graphics -- Slide animation and transition -- Viewing and navigating a slide show -- Table and charts -- Printing.
Point 2010 /, Microsoft
Keywords: MS MICROSOFT POWERPOINT